Evaluation of Rice Yield Attributes, Loach Muscle Quality, and Soil Biochemical Composition Under Rice–Loach Coculture System - Chuanqi Yu; Wenlu Zhu; Wenjun Wang; Wenqiang Xu; Yu Liu; Xingtian Cai; Yanfa Xu; Defu Yang; Zhuqing Yang; Zirui Wang; Qiubai Zhou; Haohua He (Fishes, 2026)
This study aimed to evaluate rice yield attributes, loach Paramisgurnus dabryanus muscle quality, and soil biochemical composition under rice monoculture (RM), rice–loach coculture (RLC), and loach monoculture (LM). This trial was conducted for 90 days, and then rice, fish muscle and soil were obtained for analyses. The results showed that there were no significant differences in rice yield attributes between the rice–loach coculture (RLC) and rice monoculture (RM) groups. However, rice–loach coculture (RLC) improved muscle quality-related parameters, including increased hardness and springiness of loach muscle. Meanwhile, muscle metabolomic analysis showed that all the differentially expressed metabolites (DEMs) in the significantly enriched pathways of lysine degradation and lysine biosynthesis were up-regulated in the rice–loach coculture (RLC) group compared with the loach monoculture (LM) group. Furthermore, the rice–loach coculture (RLC) improved soil physicochemical properties, including an increase in microbial biomass nitrogen (MBN) content and activities of soil N-acquiring enzymes (NAG and LAP). Moreover, soil microbiome analysis showed that the abundance of Candidatus Koribacter versatilis, Acidobacteria bacterium WX27 and Pseudolabrys taiwanensis was significantly increased in the rice monoculture (RM) and rice–loach coculture (RLC) groups compared with the loach monoculture (LM) group. Pairwise Spearman’s correlation analysis of the top 30 soil microbial species and soil physicochemical properties indicated that Terrimonas sp. H1YJ31 showed a highly significant positive correlation with the soil N-acquiring enzymes (N-acetylglucosaminidase, NAG; leucine aminopeptidase, LAP) and a soil C-acquiring enzyme (exo-β-1,4-glucanase C1), whereas Gaiella occulta, Methyloceanibacter marginalis and Anaerohalosphaera lusitana had a highly significant negative correlation with S-NAG, S-LAP and S-C1. In short, the improved fish muscle quality and soil biochemical composition were ascribed to the increased hardness and springiness of loach muscle and the abundance of soil Terrimonas sp. H1YJ31.

Retraction notice to “Targeted delivery of honokiol by zein/hyaluronic acid core-shell nanoparticles to suppress breast cancer growth and metastasis” [Carbohydr. Polym. 240 (2020) 116325 - Qi Zhang; Jing Wang; Dan Liu; Wenquan Zhu; Shuang Guan; Li Fan; Defu Cai (Carbohydrate Polymers, 2026)

Corrigendum to “Hyaluronic acid-modified liposomal honokiol nanocarrier: Enhance anti-metastasis and antitumor efficacy against breast cancer” [Carbohydr. Polym. 235 (2020) 115981] - Jing Wang; Dan Liu; Shuang Guan; Wenquan Zhu; Li Fan; Qi Zhang; Defu Cai (Carbohydrate Polymers, 2025)

Correction: Spatiotemporal characteristics and mechanisms of upper water exchange between the Arabian Sea and the Bay of Bengal in the North Indian Ocean - Defu Zheng; Junru Guo; Yanzhao Fu; Jun Song; Yu Cai (Frontiers in Marine Science, 2025)

Spatiotemporal characteristics and mechanisms of upper water exchange between the Arabian Sea and the Bay of Bengal in the North Indian Ocean - Defu Zheng; Junru Guo; Yanzhao Fu; Jun Song; Yu Cai (Frontiers in Marine Science, 2025)
The distribution of upper water masses and water exchange processes in the Arabian Sea and Bay of Bengal have important implications for the dynamics, thermal structure, and associated air-sea interactions in the North Indian Ocean. In this study, we apply the spectral clustering method to investigate the distribution patterns and exchange characteristics of Arabian Sea Water (ASW) and Bay of Bengal Water (BBW) under seasonal and interannual variability, with emphasis on the analysis of the spatiotemporal variations and control mechanisms of water fluxes in two main channel sections: the mouth of the Bay of Bengal (6° N) and the central equatorial seas (81° E). The results indicate that the eastward water flux driven by the Southwest Monsoon Current and Wyrtki jets averages 13.93±2.50 Sv (1 Sv = 10 6 /m 3 ) in summer and autumn, and the distribution range of ASW can be extended to the north of 10° N in the Bay of Bengal during this period. The winter–spring BBW incursion into the region west of 73° E in the Arabian Sea and the transport of the Northeast Monsoon Current reach 16.43±1.48 Sv, showing distinct seasonal changes. From 2001 to 2020, water fluxes across the Bay mouth and equatorial channels generally show a positive correlation. Affected by the monsoon transition process and the equatorial half-year Kelvin wave, water flux changes exhibit distinct half-year and one-year cycles. The time series of low salinity water transport anomalies and Dipole Mode Index (DMI) in the Bay mouth and equatorial region are negatively correlated (–0.30 and –0.42), indicating that water exchange is also moderated by Indian Ocean Dipole (IOD) events on the interannual scale. The equatorial region exhibits greater sensitivity to IOD events, reflecting a more complex 2–3 year cycle in water flux variations. These findings highlight the effectiveness of the spectral clustering method in revealing the spatiotemporal patterns of water masses, which is important for understanding the ocean circulation system and associated climate variability in the North Indian Ocean.

Corrigendum to “Inhibition of growth and metastasis of breast cancer by targeted delivery of 17-hydroxy-jolkinolide B via hyaluronic acid-coated liposomes” [Carbohydr. Polym. 257 (2021) 117572] - Dan Liu; Qi Zhang; Jing Wang; Shuang Guan; Defu Cai; Jicheng Liu (Carbohydrate Polymers, 2025)

Enhancing biofilm formation with powder carriers for efficient nitrogen and phosphorus removal - Yi Yang; Yuting Zhu; Defu Gan; Xiang Cai; Xiaodi Li; Xinchao Liu; Siqing Xia (Science of The Total Environment, 2024)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Development of matrix solid-phase dispersion coupled with high-performance liquid chromatography for determination of jolkinolide A and jolkinolide B in Euphorbia fischeriana Steud. - Defu Cai; Weiyu Zhai; Qi Zhang; Jianhua Liu; Yu Sun; Lei Liu; Jicheng Liu (Natural Product Research, 2017)